Studying the Effect of Tunnel Depth Variation on the Specific Energy of TBM, Case Study: KarajâTehran (Iran) Water Conveyance Tunnel - Majid Mirahmadi; Morteza Tabaei; Mohsen Soleiman Dehkordi (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
The tunnel-boring machine (TBM) is a common piece of equipment used in tunneling projects. For planning a mechanical excavation project, prediction of TBM performance and the specification of design elements such as required forces are critical. The specific energy of excavation (SE), i.e. drilling energy consumption per unit volume of rock mass, is a crucial parameter for performance prediction of a TBM. In this study, the effect of variation of tunnel depth on SE by considering the post-failure behavior of rock mass was investigated. Several new relations between SE and tunnel depth are proposed according to the statistical analysis obtained from Karaj